I have a question.
Let c = b - a and show the regression c on a has slope b hat - 1 where b hat slope from regression b on a.
answer should be b hat = SSab/SSaa - 1 (i think....)
What I want is to show that it is true. Could I please get help in answering this question.
I have attempted below.
c = b hat = SSac/SSaa
= [sum] (ai - c hat)(bi - b hat) / SSaa
= [sum] (ai - c hat)bi / SSaa - [sum] (ai - c hat)b hat / SSaa
= [sum] (ai - c hat)bi / [sum](ai-c hat) - 1
Therefore, b hat = SSab/SSaa - 1
is this correct?
Thanks for those who help me out.